Search Methodologies Introductory Tutorials in Optimization and Decision Support Techniques - Burke, Edmund K.; Kendall, Graham; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2014)
The first edition of Search Methodologies: Introductory Tutorials in Optimization and Decision Support Techniques was originally put together to offer a basic introduction to the various search and optimization techniques that students might need to use during their research, and this new edition continues this tradition. Search Methodologies has been expanded and brought completely up to date, including new chapters covering scatter search, GRASP, and very large neighborhood search. The chapter authors are drawn from across Computer Science and Operations Research and include some of the world$1 (Bs leading authorities in their field. The book provides useful guidelines for implementing the methods and frameworks described and offers valuable tutorials to students and researchers in the field. (3z(BAs I embarked on the pleasant journey of reading through the chapters of this book, I became convinced that this is one of the best sources of introductory material on the search methodologies topic to be found. The book$1 (Bs subtitle, (3z(BIntroductory Tutorials in Optimization and Decision Support Techniques(3y(B, aptly describes its aim, and the editors and contributors to this volume have achieved this aim with remarkable success. The chapters in this book are exemplary in giving useful guidelines for implementing the methods and frameworks described.(3y (BFred Glover, Leeds School of Business, University of Colorado Boulder, USA (3z(B[The book] aims to present a series of well written tutorials by the leading experts in their fields. Moreover, it does this by covering practically the whole possible range of topics in the discipline. It enables students and practitioners to study and appreciate the beauty and the power of some of the computational search techniques that are able to effectively navigate through search spaces that are sometimes inconceivably large. I am convinced that this second edition will build on the success of the first edition and that it will prove to be just as popular.(3y (BJacek Blazewicz, Institute of Computing Science, Poznan University of Technology and Institute of Bioorganic Chemistry, Polish Academy of Sciencess
Introduction -- Classical Techniques -- Integer Programming -- Genetic Algorithms -- Scatter Search -- Genetic Programming -- Artificial Immune Systems -- Swarm Intelligence -- Tabu Search -- Simulated Annealing -- GRASP: Greedy Randomized Adaptive Search Procedures -- Variable Neighborhood Search -- Very Large-Scale Neighborhood Search -- Constraint Programming -- Multi-objective Optimization -- Sharpened and Focused No Free Lunch and Complexity Theory -- Machine Learning -- Fuzzy Reasoning -- Rough-Set-Based Decision Support -- Hyper-heuristics -- Approximations and Randomization -- Fitness Landscapes.
Keywords: Economics; Electronic data processing; Operations research; Economics/Management Science; Operation Research/Decision Theory; Operations Research, Management Science; Computing Methodologies